Let's meet Taylor - Koken, Alexandra; Baker, Claire; Avila Lagunes, Mariana (New York, NY : Kingfisher, 2024)
Young readers can learn about superstar, gifted singer-songwriter Taylor Swift. They can read about her inspirational journey to superstardom, showing why she believes everyone should have the chance to be who they want to be.
Story of the superstar Taylor Swift--Cover.
An unofficial biography for her young fans--Cover.
K-3
Keywords: Swift, Taylor, -- 1989- -- Juvenile literature; Women singers -- United States -- Biography -- Juvenile literature; Singers -- United States -- Biography -- Juvenile literature; Swift, Taylor, -- 1989-; Women singers; Singers; Women -- Biography; Biographies; Nonfiction picture books